2015
DOI: 10.1038/npp.2015.271
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Modafinil Treatment Effects on Control-Related Gamma Oscillatory Power in Schizophrenia

Abstract: Control-related cognitive processes such as rule selection and maintenance are associated with cortical oscillations in the gamma range, and modulated by catecholamine neurotransmission. Control-related gamma power is impaired in schizophrenia, and an understudied treatment target. It remains unknown whether pro-catecholamine pharmacological agents augment control-related gamma oscillations in schizophrenia. We tested the effects of 4-week fixed-dose daily adjunctive modafinil (MOD) 200 mg, in a randomized dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 62 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The mechanism of action underlying this effect remains to be determined however. The pro-cognitive effects of modafinil may arise from its ability to facilitate middle frequency cortical oscillations (theta, alpha, beta) acutely (Minzenberg et al, 2014a, 2014b), or higher frequency cognitive-control related activity (gamma) with sustained treatment (Minzenberg et al, 2016). Further, McKenna and colleagues (McKenna et al, 2013) identified numerous regions underlying 5C-CPT performance using fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of action underlying this effect remains to be determined however. The pro-cognitive effects of modafinil may arise from its ability to facilitate middle frequency cortical oscillations (theta, alpha, beta) acutely (Minzenberg et al, 2014a, 2014b), or higher frequency cognitive-control related activity (gamma) with sustained treatment (Minzenberg et al, 2016). Further, McKenna and colleagues (McKenna et al, 2013) identified numerous regions underlying 5C-CPT performance using fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving other neurotransmitters support the notion that the effects of E/I imbalance are more widespread than initially believed. Compounds targeting dopaminergic and norepinephrinergic neurons typically increase evoked gamma power (23,24), indicating that these neurotransmitters can be indirectly surveilled using this measurement technique. Preclinical evidence in rodents also suggests that ASSR also changes in response to cholinergic neurotransmitter modulation (25).…”
Section: Gamma Oscillations In Understanding Disease Etiologymentioning
confidence: 99%
“…Using an alpha-7 nicotinic receptor agonist, Keefe and colleagues [ 19 ] showed significant improvement in performance on the CogState battery [ 20 ] with relatively small effect sizes (Cohen’s d = 0.26), but no significant improvement on the Measurement And Treatment Research to Improve Cognition in Schizophrenia (MATRICS) battery [ 21 ]. Although administration of a generalized attention-enhancing agent (modafinil) with an uncertain mechanism of action elicited enhanced cortical gamma-range oscillatory power [ 22 ], other studies [ 23 ] failed to find significant differences between modafinil treatment and placebo on assays of trained tasks and cognitive measures from the MATRICS battery. Given that cognitive deficits are related to functional impairment, which prevents full recovery, and that no effective pharmacological treatments for cognitive deficits are presently available, there remains an urgent need to identify novel pharmacological treatments to reverse cognitive deficits in people with schizophrenia.…”
Section: Neurocognitive Deficits In Patients With Schizophrenia and mentioning
confidence: 99%